COMPLEX METAPHOR - Kemertelidze, Nino; Manjavidze, Tamar (European Scientific Journal, ESJ, 2014)
Metaphor has always been attracting researchers’ attention. A lot of things have been written and are still being written about this phenomenon in philosophy, psychology, linguistics and literary theory, because metaphor is one of the crucial topics in contemporary science. Linguistics always considered it as means of filling the gaps existing in language and enriching the speech. Metaphor is based on the principle of identification. It becomes stylistic device when two completely different phenomena/ things/ events are united in the mind according to a certain feature, which one of them does not possess in reality. It happens when the creator of metaphor finds something in common in two presented things.